2016
DOI: 10.1093/neuonc/now270
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance perfusion image features uncover an angiogenic subgroup of glioblastoma patients with poor survival and better response to antiangiogenic treatment

Abstract: Our findings suggest that an angiogenic subtype of GBM patients may benefit from antiangiogenic therapy with improved overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 33 publications
4
33
0
Order By: Relevance
“…Subtype classification problems are not unique to adult gliomas, however. Conceptually similar work has been done on other brain tumors, in which it has been demonstrated that classification algorithms trained on radiomics features extracted from conventional MRI can generate predictive models for pituitary adenoma subtypes and pediatric brain tumors (Table ) …”
Section: Cns Tumor Imagingmentioning
confidence: 93%
See 3 more Smart Citations
“…Subtype classification problems are not unique to adult gliomas, however. Conceptually similar work has been done on other brain tumors, in which it has been demonstrated that classification algorithms trained on radiomics features extracted from conventional MRI can generate predictive models for pituitary adenoma subtypes and pediatric brain tumors (Table ) …”
Section: Cns Tumor Imagingmentioning
confidence: 93%
“…Imaging plays an important role in the initial diagnosis of brain tumors and is a routine part of both initial and subsequent evaluation. The complex imaging features of brain tumors, as well as the frequent genetic heterogeneity within tumor types and the invasive nature of the procedures needed to obtain a tissue diagnosis, give rise to diagnostic dilemmas in this field (Table ) …”
Section: Cns Tumor Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Cerebral blood volume (CBV) and cerebral blood flow (CBF) maps were obtained through the standard algorithm proposed by Liu et al 32 Only concentration-time curves with signal-to-noise ratio greater than 5 and a goodness of fit R 2 > 0.95 to the bivariate gamma function were quantified. A post-processing technique based on the leakage correction method of Boxerman et al 33 was used to correct for over-and under-estimations of CBV and CBF markers.…”
Section: Dsc Quantification and Hts Analysismentioning
confidence: 99%